Reference Values for Physical Performance Measures in the Aging Working Population. (February 2014) - Cote, Mark; Kenny, Anne; Dussetschleger, Jeffrey; Farr, Dana; Chaurasia, Ashok; Cherniack, Martin
Objective: The aim of this study was to determine reference physical performance values in older aging workers. Background: Cross-sectional physical performance measures were collected for 736 manufacturing workers to assess effects of work and nonwork factors on age-related changes in musculoskeletal function and health. Method: Participants underwent surveys and physical testing that included bioelectrical impedance analysis, range-of-motion measures, exercise testing, and dynamic assessment. Results: Physical characteristics, such as blood pressure and body fat percentage, were comparable to published values. Dynamic and range-of-motion measurements differed from published normative results. Women had age-related decreases in cervical extension and lateral rotation. Older men had better spinal flexion than expected. Predicted age-related decline in lower-extremity strength and shoulder strength in women was not seen. Men declined in handgrip, lower-extremity strength, and knee extension strength, but not trunk strength, across age groups. There was no appreciable decline in muscle fatigue at the trunk, shoulder, and knee with aging for either gender, except for the youngest age group of women. Conclusion: Normative values may underestimate physical performance in "healthy" older workers, thereby underappreciating declines in less healthy older workers. Work may be preservative of function for a large group of selected individuals. A "healthy worker effect" may be greater for musculoskeletal disease and function than for heart disease and mortality. Application: Clinicians and researchers studying musculoskeletal function in older workers can use a more specific set of reference values.